Evidence and rational based research on Chinese Drugs - Ulrich-Merzenich, Gudrun; Wagner, Hildebert (Springer Vienna, 2013)
After the successful introduction of acupuncture to the West, recent advances in analytical methods in chemistry, molecular biology and system biology - especially the development of the "omic" technologies - have again brought Chinese drugs into the focus of research on Traditional Chinese Medicine (TCM). With more than 1000 publications on the chemistry, molecular biology and pharmacology of TCM drugs in international journals over the last 10 years, Chinese drugs are gaining increasingly reputation and impact. These data offer great opportunities for the development of new pharmaceuticals for various clinical applications. International Scientists have compiled relevant and trend setting research results in this book. Topics range from the latest methods of quality and safety assurance by chemical and genetic fingerprints to the development of new pharmaceuticals for a future evidence-based therapy e.g. for cancer, cardiovascular, inflammatory or infectious diseases as well as to recent experimental results on multitarget and synergy research for the preparation of multi-extract-pharmaceuticals from TCM.